Quality of life amongst lymphoma survivors in a developing country - Ng Diana L.C; Leong Y.C.; Gingin Gan (Springer Verlag, 2016)
Purpose: The survival for patients with lymphoma has improved over the past decades with the introduction of novel agents. Quality of life of these survivors is now being studied with focus on minimising the late effects of chemotherapy and improving psychosocial support. This study aims to determine the prevalence of anxiety and depression of lymphoma survivors and to investigate the possible association between these disorders and quality of life. Methods: Patients with previous diagnosis of lymphoma who remained in remission were recruited from a major hospital in Malaysia. Quality of life of these patients was measured using European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ C30). Anxiety and depression symptoms were assessed using Hospital Anxiety and Depression scale (HADS). Results: A total of 156 patients participated in this study. Eighteen percent (18 %) of patients had symptoms of anxiety, and 10 % had symptoms of depression. Patients who had higher depression scores were older, of lower education level and had more than one comorbidity illness. Patients with anxiety were associated with lower overall quality of life (QOL) score, lower emotional and cognitive functioning and complained more of fatigue and insomnia (p < 0.05). Patients who had depression were associated with lower physical functioning and complained more of insomnia (p < 0.05). Conclusion: It is important for the treating physicians to ensure follow-up of lymphoma survivors for any psychological disorders in order early counseling and support can be provided. This may improve patients’ quality of life.